Role of tiotropium in chronic obstructive pulmonary disease exacerbation - Pant, P; Yadav, B; Khan, GM; Koju, R; Gurung, R; Pokharel, B; Bedi, TRS; Adkhari, RK (Journal of Institute of Medicine Nepal, 2011)
Introduction: Chronic obstructive pulmonary disease (COPD) remains a major public health problem. Many patients suffering from chronic obstructive lungs diseases are of poor economic status, mostly illiterate, therefore has a direct bearing on patient compliance. Tiotropium is a new anticholinergic therapy for chronic obstructive pulmonary disease that differs from ipratropium by its functional relative selectively for musarinic receptor subtypes and which allows single dosing a day. This study presents a cost-effectiveness, efficacy, and side-effects of Ipratropium bromide and Tiotropium in COPD. Methods: Prospective study was conducted In Kathmandu University Teaching Hospital, between the year 2008 and 2009 in terms of cost-effectiveness, efficacy, and side-effects of Tiotropium and Ipratropium amongst COPD patients. Results: Tiotropium and Ipratropium were prescribed in total of 57 patients (30 in ipratropium bromide and 27 in tiotropium bromide) for the management of COPD among outpatients. There were no significant differences in age, height, weight and baseline lung function parameters (FEV1 and PEF) between the two drugs i.e. ipratropium bromide and tiotropium bromide. Significant improvement in lung function parameters were found in each respective group of drugs after bronchodilator therapy. Tiotropium results in significant reduction of Chronic Obstructive Pulmonary disease exacerbations and significant improvement in quality of life, lung function, and dyspnoea compared to ipratropium. The additional cost to achieve these favorable outcomes was cheaper than Ipratropium bromide. (Nepalese Rs. 7.03 per day for tiotropium as compared to Rs. 9.06 for Ipratropium) Conclusions: Tiotropium results in significant reduction of chronic obstructive pulmonary disease exacerbations and significant improvement in quality of life, lung function and dyspnoea compared to Ipratropium. Keywords: Chronic obstructive pulmonary disease; ipratropium; tiotropium DOI: http://dx.doi.org/10.3126/joim.v32i2.4937 Journal of Institute of Medicine, August, 2010; 32: 5-10